Multi-criteria decision making: An example of sensitivity analysis - Pamučar, Dragan S.; Božanić, Darko; Ranđelović, Aca (Serbian Journal of Management, 2016)
This study provides a model for result consistency evaluation of multicriterial decision making (MDM) methods and selection of the optimal one. The model is based on the analysis of results of MDM methods, that is, the analysis of changes in rankings of MDM methods that occur as a result of alterations in input parameters. In the recommended model, we examine sensitivity analysis of MDM methods to changes in criteria weight and result consistency of methods to changes in measurement scale and the way in which we formulate criteria. In the final phase of the model, we select the most suitable method to solve the observed problem and the optimal alternative. The model is tested on an example, when the optimal MDM method selection was required in order to determine the location of the logistical center. During the selection process, TOPSIS, COPRAS, VIKOR and ELECTRE methods were considered. VIKOR method demonstrated the biggest stability of rankings and was selected as the most fit method for ranking the locations of the logistical center. Results of the demonstrated analysis indicate sensitivity of standard MDM methods to criteria considered in this work. Therefore, it is necessary, to take into account stability of the considered method during the selection process of the optimal method.